1996
DOI: 10.1128/jcm.34.5.1147-1152.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three commercial enzyme immunoassays compared with the 13C urea breath test for detection of Helicobacter pylori infection

Abstract: The diagnostic significance of the serological detection of antibodies to Helicobacter pylori has been established by numerous investigators. Reports of the clinical reliabilities of commercial enzyme immunoassay (EIA) kits available for this purpose vary as a result of the different H. pylori antigen sources and reference methods used. The 13 C urea breath test (UBT) has been shown to be an extremely accurate and reliable method of detecting H. pylori infection. We used the 13 C urea breath test as the confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The GAP IgG test has a wide grey zone of 19%; this is echoed by other investigators demonstrating grey zones of 17.3% and 12%, bringing the accuracy of the test into question 11 , . 5 Two studies reported specificities of 26% and 29%, with another reporting a sensitivity of only 50% 11 , . 12 , 13 …”
Section: Discussionmentioning
confidence: 90%
“…The GAP IgG test has a wide grey zone of 19%; this is echoed by other investigators demonstrating grey zones of 17.3% and 12%, bringing the accuracy of the test into question 11 , . 5 Two studies reported specificities of 26% and 29%, with another reporting a sensitivity of only 50% 11 , . 12 , 13 …”
Section: Discussionmentioning
confidence: 90%
“…Meijer et al (15) compared eight commercial kits and suggested that these kits may be useful in diagnosing H. pylori infection in addition to biopsy-based methods. Similarly, Lozniewski et al (12), Marchildon et al (13), and Chen et al (6) reported the usefulness of serodiagnosis for detecting H. pylori infection. Furthermore, Nilsson et al (20) described an immunoblot assay using acid glycineextracted cell surface proteins of H. pylori that included 110/120 kDa and some low molecular mass proteins as antigens.…”
mentioning
confidence: 94%
“…On the other hand, noninvasive serology and 13 Curea breath test have the same diagnostic accuracies as biopsy-based tests for detecting H pylori infection. 4,5 Because the serum immunoglobulin G (IgG) test has showed high sensitivity and specificity, 6,7 the serology test has been used widely in epidemiologic studies and routine diagnosis of H pylori infection. Although most previous serologic studies have used noncommercial enzyme immunoassay (EIA) methods for IgG antibodies to H pylori, several commercial EIA kits are now available.…”
mentioning
confidence: 99%
“…Although most previous serologic studies have used noncommercial enzyme immunoassay (EIA) methods for IgG antibodies to H pylori, several commercial EIA kits are now available. 7,8 Generally, it is thought that H pylori infection persists for a lifetime and that the serum IgG antibody level remains high. Although spontaneous elimination of H pylori can occur, it is infrequent.…”
mentioning
confidence: 99%